2021
DOI: 10.1038/s41598-021-97375-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extreme (flat and steep) keratometry on the safety and efficacy of small incision lenticule extraction (SMILE)

Abstract: Little is known about the connection between preoperative keratometry and postoperative results of myopic small-incision lenticule extraction (SMILE). To determine the influence of extreme (flat and steep) corneal keratometry on the safety and efficacy of SMILE, the databases of the Department of Ophthalmology, Ludwig-Maximilians-University Munich, Germany, and SMILE Eyes Linz, Austria, were screened for patients with steep and flat keratometry who had undergone SMILE. In this cross-sectional matched comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…11 Similarly, Luft et al showed noninferior outcomes for flat and steep corneas after SMILE. 12 In this study, all 3 groups had high efficacy and safety indexes with no significant differences between the groups and were comparable with previous studies. In all groups, at least 96% of patients had no change in or gained 1 or 2 lines in CDVA with 0% to 1% who lost 2 lines in CDVA, with no significant difference between all 3 groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…11 Similarly, Luft et al showed noninferior outcomes for flat and steep corneas after SMILE. 12 In this study, all 3 groups had high efficacy and safety indexes with no significant differences between the groups and were comparable with previous studies. In all groups, at least 96% of patients had no change in or gained 1 or 2 lines in CDVA with 0% to 1% who lost 2 lines in CDVA, with no significant difference between all 3 groups.…”
Section: Discussionsupporting
confidence: 90%
“…[8][9][10] Studies evaluating steep and flat corneas before a SMILE procedure have showed comparable postoperative results. 11,12 The aforementioned studies focused on myopic LASIK or SMILE and not PRK.…”
mentioning
confidence: 99%
“…The K value was used as the target metric for determining corneal curvature, which averages the flat meridian (K1) and steep meridian (K2) measured by keratometry. A flat cornea was defined as a K value of 42.0 D or below, a regular cornea as K value between 42.0 and 45.0 D, and a steep cornea as K value of 45.0 or greater [ 17 ]. This categorization has been adopted in previous studies to predict different postoperative prognoses according to corneal curves [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…A flat cornea was defined as a K value of 42.0 D or below, a regular cornea as K value between 42.0 and 45.0 D, and a steep cornea as K value of 45.0 or greater [ 17 ]. This categorization has been adopted in previous studies to predict different postoperative prognoses according to corneal curves [ 17 , 18 ]. When analyzing the keratometry values, eight eyes were excluded from the original test set ( N = 142 eyes) due to missing values.…”
Section: Methodsmentioning
confidence: 99%